IMAGING OF A RARE CASE OF MULLERIAN DUCT ANOMALY IN AN AMENORRHEIC WOMAN: A CASE SERIES - Nabilla Hardiyanti, Ginanda; Nurdiana, Farah; Yueniwati, Yuyun (International Journal of Radiology and Imaging, 2024)
Müllerian duct anomalies encompass a range of conditions that can lead to primary amenorrhea, infertility, and complications during pregnancy. Uterus didelphys arise when the Müllerian ducts fail to fuse properly to form a single uterus. In contrast, a septate uterus occurs when the central septum between the ducts fails to resorb. We describe three cases: the first involves a 14-year-old girl experiencing lower abdominal pain and secondary amenorrhea; MRI revealed a completely septate uterus with OHVIRA. The second case is a 27-year-old woman with secondary amenorrhea and primary infertility, who also had a complete septate uterus on MRI. The third case concerns a 17-year-old girl with primary amenorrhea, whose MRI showed uterus didelphys and a single left kidney. Müllerian duct anomalies are present in up to 7% of women, and about one-third of these women also have renal anomalies. Septate uterus is the most common type of Müllerian anomaly, while uterus didelphys is relatively rare. A complete septate uterus with obstructed hemivagina and an associated renal anomaly is particularly uncommon. Advances in diagnostic and surgical methods aim to preserve or enhance reproductive potential. Keywords: Uterus didelphys, septate uterus, OHVIRA